Learn more about

Refine search

Results (displaying matches 1-50 of 20105)  Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
1008.a.27216.1 1008.a \(y^2 + (x^3 + x)y = -4x^4 + 15x^2 - 21\) $G_{3,3}$ 0
1012.a.4048.1 1012.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1038.a.1038.1 1038.a \(y^2 + (x^2 + x)y = x^5 - 12x^4 + 26x^3 + 46x^2 + 21x + 3\) $\mathrm{USp}(4)$ 0
1038.a.1038.2 1038.a \(y^2 + (x^3 + 1)y = x^4 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ 0
1042.a.1042.1 1042.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 + 2x + 2\) $\mathrm{USp}(4)$ 0
1047.a.3141.1 1047.a \(y^2 + (x^3 + x)y = x\) $\mathrm{USp}(4)$ 0
1050.a.131250.1 1050.a \(y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3\) $G_{3,3}$ 0
1051.a.1051.1 1051.a \(y^2 + y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1051.b.1051.1 1051.b \(y^2 + (x + 1)y = -x^5 - x^4\) $\mathrm{USp}(4)$ 0
1051.b.1051.2 1051.b \(y^2 + xy = x^5 + 8x^4 + 16x^3 + x\) $\mathrm{USp}(4)$ 0
1055.a.1055.1 1055.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - x - 1\) $\mathrm{USp}(4)$ 0
1062.a.6372.1 1062.a \(y^2 + (x^3 + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1069.a.1069.1 1069.a \(y^2 + (x^2 + x + 1)y = x^5 + x^3\) $\mathrm{USp}(4)$ 0
1070.a.2140.1 1070.a \(y^2 + (x^3 + 1)y = x^3 - x\) $\mathrm{USp}(4)$ 1
1077.a.1077.1 1077.a \(y^2 + (x^3 + 1)y = 5x^5 + 34x^4 + 80x^3 - x^2 - 90x + 32\) $\mathrm{USp}(4)$ 1
1077.a.1077.2 1077.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
1077.b.1077.1 1077.b \(y^2 + x^3y = x^5 + x^4 - x - 2\) $\mathrm{USp}(4)$ 0
1077.b.1077.2 1077.b \(y^2 + y = x^5 + 14x^4 + 38x^3 - 79x^2 + 15x - 1\) $\mathrm{USp}(4)$ 0
1083.a.1083.1 1083.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3\) $G_{3,3}$ 1
1083.a.20577.1 1083.a \(y^2 + x^3y = x^5 - 5x^4 + 11x^3 - 13x^2 + 9x - 3\) $G_{3,3}$ 1
1083.b.87723.1 1083.b \(y^2 + y = -x^6 - 3x^5 - 8x^4 - 11x^3 - 14x^2 - 9x - 6\) $G_{3,3}$ 0
1083.b.390963.1 1083.b \(y^2 + y = -x^6 + 3x^5 - 50x^4 + 95x^3 - 14x^2 - 33x - 6\) $G_{3,3}$ 0
1088.a.1088.1 1088.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + 2x^2 + x + 1\) $N(G_{3,3})$ 0
1088.b.2176.1 1088.b \(y^2 + (x^3 + x)y = 4x^4 + 24x^2 + 34\) $N(G_{1,3})$ 0
1088.b.2176.2 1088.b \(y^2 + (x^3 + x)y = -5x^4 + 24x^2 - 34\) $N(G_{1,3})$ 0
1091.a.1091.1 1091.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1094.a.2188.1 1094.a \(y^2 + (x^3 + 1)y = x^4 - x^2\) $\mathrm{USp}(4)$ 1
1104.a.17664.1 1104.a \(y^2 = x^5 - 2x^4 + 4x^3 - 4x^2 + 3x - 1\) $\mathrm{USp}(4)$ 0
1104.b.141312.1 1104.b \(y^2 + (x^3 + x)y = -x^6 - 3x^4 + 29x^2 - 46\) $G_{3,3}$ 0
1109.a.1109.1 1109.a \(y^2 + y = x^5 - 6x^4 - 36x^3 - 6x^2 + 63x - 36\) $\mathrm{USp}(4)$ 0
1109.b.1109.1 1109.b \(y^2 + y = x^5 - x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1109.c.1109.1 1109.c \(y^2 + (x^3 + x)y = x^5 - 2x^3 - 2x^2 - 1\) $\mathrm{USp}(4)$ 0
1116.a.214272.1 1116.a \(y^2 + (x^3 + 1)y = x^4 + 2x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
1122.a.1122.1 1122.a \(y^2 + (x^2 + x)y = x^5 + 7x^4 - 43x^2 + 51x - 17\) $G_{3,3}$ 0
1122.b.2244.1 1122.b \(y^2 + (x^2 + x)y = x^5 + 7x^4 + 5x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1123.a.1123.1 1123.a \(y^2 + (x^3 + x)y = -x^4 - x^2 - x\) $\mathrm{USp}(4)$ 0
1125.a.151875.1 1125.a \(y^2 + xy = 15x^5 + 50x^4 + 55x^3 + 22x^2 + 3x\) $G_{3,3}$ 0
1127.a.1127.1 1127.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 1
1136.a.9088.1 1136.a \(y^2 + (x^3 + x)y = x^4 - x^3 + 2x^2 - x + 1\) $\mathrm{USp}(4)$ 0
1136.a.290816.1 1136.a \(y^2 + (x^3 + x^2)y = -5x^4 - 9x^3 + 25x^2 + 40x - 24\) $\mathrm{USp}(4)$ 0
1137.a.1137.1 1137.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 + x^3\) $\mathrm{USp}(4)$ 0
1142.a.2284.1 1142.a \(y^2 + (x^3 + x^2)y = -x^4 - x^3 + x^2 - x - 2\) $\mathrm{USp}(4)$ 0
1142.b.9136.1 1142.b \(y^2 + (x + 1)y = -x^5 + 3x^4 - 6x^2 + x + 3\) $\mathrm{USp}(4)$ 0
1145.a.1145.1 1145.a \(y^2 + (x^3 + 1)y = -3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 1
1145.a.143125.1 1145.a \(y^2 + (x^3 + x^2 + x)y = 2x^4 + 4x^3 + 9x^2 + 10x + 9\) $\mathrm{USp}(4)$ 1
1146.a.2292.1 1146.a \(y^2 + xy = x^5 + 3x^4 + 5x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
1147.a.35557.1 1147.a \(y^2 + xy = x^5 + 8x^4 + 18x^3 + 8x^2 + x\) $\mathrm{USp}(4)$ 0
1147.a.35557.2 1147.a \(y^2 + xy = x^5 + 6x^4 - 32x^2 + x\) $\mathrm{USp}(4)$ 0
1148.a.8036.1 1148.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 6x^3 + x^2 + 5x - 1\) $\mathrm{USp}(4)$ 0
1148.a.47068.1 1148.a \(y^2 + (x^2 + x + 1)y = x^5 + 2x^4 - 5x^3 + x\) $\mathrm{USp}(4)$ 0
Next
Download all search results for